The effect of math self-concept and self-efficacy on the math achievement of sixth-grade primary school students: the mediating role of math anxiety - Ruijia, Zuo; Talib, Othman; Burhanuddin, Nur Aimi Nasuha; Wenling, Li (Human Resource Management Academic Research Society, 2022)
The relationship between math self-concept, self-efficacy, math anxiety, and math achievement was investigated using 450 sixth-grade students in Sichuan Province, China as subjects. The results showed that: math self-concept and self-efficacy positively predicted students’ math achievement, and math anxiety negatively predicted students’ math achievement. Mathematics anxiety played a partial mediating role in the relationship between mathematics self-concept and mathematics achievement, mathematics self-efficacy, and mathematics achievement. Mathematical self-efficacy and math anxiety played a mediating chain role in the relationship between math self-concept and math achievement. To improve students' math achievement, it is necessary to pay attention to the positive significance of math self-concept and self-efficacy and reduce the adverse effects of math anxiety.